Questions de pratiquants et réponses d’imam en contexte français - Cédric Baylocq Sassoubre (Revue des Mondes Musulmans et de la Méditerranée)
This study focuses an ethnographic lens on how young French Muslims, locally and interactively among peer groups, interact with local religious authorities in constructing their religious practices. The context is a reappraisal of Islamic law by Imam Tareq Oubrou, mufti of the mosque in Bordeaux. In this study we isolated a particular moment in the religious dialogue between the imam and the faithful, the so-called “legal consultation” which follows the sermon during Friday evening prayers (the khotba during salat el jomou’a) in order to better understand the imam’s role in constructing youthful religious identities. Five sessions dealing with religious dogma as well as with family and professional matters confronting these young practitioners were recorded, transcribed and analysed. What questions do these young people submit to the imam? How does the imam’s legal advice account for the secular space in which he practices his faith? To the extent that it can be measured, what is the impact of the fatwa pronounced by the imam on the life of the supplicant? This study is the outcome of an innovative theologico-canonical approach which emerges over the course of the study.